Computational engineering analysis of external geometrical modifications on the MQ-1 unmanned combat aerial vehicle - Bagul, Prakash; Rana, Zeeshan A.; Jenkins, Karl W.; Könözsy, László Z. (Elsevier, 2020)
This paper focuses on the effects of external geometrical modifications on the aerodynamic characteristics of the MQ-1 predator Unmanned Combat Aerial Vehicle (UCAV) using computational fluid dynamics. The investigations are performed for 16 flight conditions at an altitude of 7.6 km and at a constant speed of 56.32 m/s. Two models are analysed, namely the baseline model and the model with external geometrical modifications installed on it. Both the models are investigated for various angles of attack from −4° to 16°, angles of bank from 0° to 6° and angles of yaw from 0° to 4°. Due to the unavailability of any experimental (wind tunnel or flight test) data for this UCAV in the literature, a thorough verification of calculations process is presented to demonstrate confidence level in the numerical simulations. The analysis quantifies the loss of lift and increase in drag for the modified version of the MQ-1 predator UCAV along with the identification of stall conditions. Local improvement (in drag) of up to 96% has been obtained by relocating external modifications, whereas global drag force reduction of roughly 0.5% is observed. The effects of external geometrical modifications on the control surfaces indicate the blanking phenomenon and reduction in forces on the control surfaces that can reduce the aerodynamic performance of the UCAV.
Keywords: Aerodynamics; CFD; Geometrical modifications; GMQ-1 predator; Turbulent flows; Unmanned combat aerial vehicle; Unsteady Reynolds-averaged Navier-Stokes